Penerapan Metode Pembelajaran “Active Learning-Small Group Discussion” di Perguruan Tinggi Sebagai Upaya Peningkatan Proses Pembelajaran - Endah Syamsiyati Nur Jannah (FONDATIA, 2019)
The active learning approach that is carried out in the subject of Student Development in the Faculty of Islamic Sciences majoring in PAI at the Islamic University of Indonesia in the 4th semester, aims to improve student learning activeness with non-monotonous learning strategies. With this learning method, students can actively explore themselves by finding the main ideas in solving a problem, or students can apply what is learned in real life. Several learning methods can be used as alternatives to increase student activity during the learning process, one of them is "Active Learning Methods-Small Group Discussion". This study uses a qualitative descriptive analysis by collecting data through observation and documentation. The results of this research method of active learning with a group discussion or small group discussion can increase learning activeness involving fourth-semester students of class D in the subject of the development of PAI FIAI UII Yogyakarta students in terms of the theories put forward by experts.